2012
DOI: 10.1136/bmjopen-2011-000312
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study examining whether neurological deficits and PTSD in combat veterans are related to episodes of mild TBI

Abstract: BackgroundMild traumatic brain injury (mTBI) is a common injury among military personnel serving in Iraq or Afghanistan. The impact of repeated episodes of combat mTBI is unknown.ObjectiveTo evaluate relationships among mTBI, post-traumatic stress disorder (PTSD) and neurological deficits (NDs) in US veterans who served in Iraq or Afghanistan.MethodsThis was a case–control study. From 2091 veterans screened for traumatic brain injury, the authors studied 126 who sustained mTBI with one or more episodes of loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 63 publications
4
68
0
Order By: Relevance
“…The proportion of Veterans who screened positive for TBI and also had PTSD was more than twice the proportion that screened negative for TBI and also had PTSD (32% vs 13%). Our findings are consistent with previous studies that have also found an association between mild TBI and PTSD with about 40 percent of individuals with combat-related mild TBI also having PTSD [2,[31][32]. Our study included some patients with more severe TBI, and it has been previously found that the risk of developing PTSD may be higher for a Veteran with combat-related mild TBI than severe TBI [33].…”
Section: Discussionsupporting
confidence: 82%
“…The proportion of Veterans who screened positive for TBI and also had PTSD was more than twice the proportion that screened negative for TBI and also had PTSD (32% vs 13%). Our findings are consistent with previous studies that have also found an association between mild TBI and PTSD with about 40 percent of individuals with combat-related mild TBI also having PTSD [2,[31][32]. Our study included some patients with more severe TBI, and it has been previously found that the risk of developing PTSD may be higher for a Veteran with combat-related mild TBI than severe TBI [33].…”
Section: Discussionsupporting
confidence: 82%
“…False positive screens for TBI may occur if the Veteran has other conditions, including PTSD or other conditions that have concussion-like symptoms, such as hearing loss and vestibular changes [21]. The proportion of screened TBI Veterans who completed a secondary TBI assessment and subsequently received a physician diagnosis of TBI was 53 percent, which is consistent with the proportion of approximately 60 percent found in other studies [22][23]. The reported symptom prevalence was similar in both the screened TBI and the confirmed TBI groups (70% vs 72%).…”
Section: Discussionsupporting
confidence: 78%
“…Approximately 1.7 million individuals sustain a TBI each year and over 3.2 million people are living with the long-term effects of this injury [4,5]. It has been suggested that these numbers maybe under-reported due to those with mild TBI not seeking medical attention [6]. In addition, these numbers do not account for brain injuries treated in military treatment facilities, during deployment and in Veterans Affairs hospitals.…”
Section: Traumatic Brain Injurymentioning
confidence: 97%